2022
DOI: 10.3390/molecules27196680
|View full text |Cite
|
Sign up to set email alerts
|

Antibacterial and Antifungal Silver Nanoparticles with Tunable Size Embedded in Various Cellulose-Based Matrices

Abstract: The aim of this study was to synthesize silver nanoparticles (AgNPs) using cellulose derivatives and to evaluate their antimicrobial potential. As effective reducing and stabilizing agents for AgNPs, cellulose derivatives, such as hydroxypropyl cellulose (HPC), methylcellulose (MC), ethylcellulose (EC), and cellulose acetate (CA), were used. Their ability to reduce silver ions as well as the size of the resulting AgNPs were compared. The formation and stability of the reduced AgNPs in the solution were monitor… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
5
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(6 citation statements)
references
References 35 publications
1
5
0
Order By: Relevance
“…This fact indicates that the density of polymer aggregates in the solution with AgNO 3 was higher than the density of clusters in the ion-free solution. This conclusion is confirmed by the results of works [13][14][15][16][17], where it was shown that silver nitrate is reduced by cellulose derivatives to metal; as a result, polymer aggregates contain silver nanoparticles tens of nanometers in size.…”
Section: Dilute (1 : 10) Solutions Light Reflectionsupporting
confidence: 66%
See 2 more Smart Citations
“…This fact indicates that the density of polymer aggregates in the solution with AgNO 3 was higher than the density of clusters in the ion-free solution. This conclusion is confirmed by the results of works [13][14][15][16][17], where it was shown that silver nitrate is reduced by cellulose derivatives to metal; as a result, polymer aggregates contain silver nanoparticles tens of nanometers in size.…”
Section: Dilute (1 : 10) Solutions Light Reflectionsupporting
confidence: 66%
“…In our opinion, the aggregation and sedimentation of polymer clusters from dilute solutions in the presence of ions has an important application value for the development of promising technologies, such as catalysts with adjustable activity and film nanocomposite materials [36][37][38][39][40]. In works [13][14][15][16][17], it was shown that composite films based on water-soluble cellulose derivatives with metallic silver nanoparticles have a high fungicidal and antibacterial efficiencies against both gram-positive and gram-negative bacteria. Taking this fact into account, the aggregation in diluted aqueous solutions of HPC with the ions of NaI and AgNO 3 salts can be used in modern technologies for the production of bactericidal polymeric films used for wound treatment.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Notably, the in situ synthesis optimizes the rate of MNPs formation. However, it showed poor control of morphology and polydispersity of the resulting NPs on the cellulose fibers [63] , [64] , [65] , [66] , [67] . For instance, He et al used paper as a substrate for generating MNPs using AgNO 3 as a precursor and NaBH 4 as a reducing agent.…”
Section: Introductionmentioning
confidence: 99%
“…Different research has modified cellulose surfaces by wet impregnating previously synthesized and in situ MNPs, thus taking advantage of cellulose wetting and porosity in water [63] , [64] , [65] , [66] , [67] . As a general procedure, cellulose paper is immersed in the metal salt solution.…”
Section: Introductionmentioning
confidence: 99%